Peran Program Business Challenge sebagai Sarana Pemberdayaan Ekonomi dan Pembentukan Karakter Islami Remaja Masjid Nurul Yaqin di Tanah Enam Ratus - Olivia Shafitri; Muhammad Arifin Lubis (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2025)
This study aims to describe the role of the Business Challenge program as a means of economic empowerment and Islamic character formation among the youth of Nurul Yaqin Mosque in Tanah Enam Ratus. The main issue focuses on the extent to which this activity enhances participants’ economic independence, creativity, and Islamic values. This research employs a descriptive qualitative approach with data collected through interviews, observations, and documentation involving program committees, mentors, and participants. The findings reveal that the Business Challenge program plays a significant role in fostering youth entrepreneurship through Sharia-based business practices, basic financial management, and teamwork rooted in the values of trustworthiness, discipline, and responsibility. Moreover, it strengthens the participants’ Islamic character, such as honesty, independence, and social concern. Therefore, the Business Challenge serves not only as an economic training platform but also as a medium for shaping a productive and morally upright generation of mosque youth.